Diversidad de agentes polinizadores y su influencia en la producción de cacao (theobroma cacao l.), tipo nacional en monocultivo y sistema agroforestal en la Finca Experimental “La Represa” - Armijos Vásquez, Vivianna Estefanía (2016)
This research project was conducted at the Experimental Farm "La Represa" property of the State Technical University of Quevedo, located at Kilometer 7.5 of Via Quevedo- San Carlos, on the grounds Faita, Province of Los Rios. The overall objective was to determine the diversity of pollinators of cocoa (Theobroma cacao L.) National Type in monoculture and agroforestry system of the Experimental Farm "La Represa". It was placed randomly based stubble traps and Musáceas in T. cacao plants established in monoculture and agroforestry system. collection of insects three times a week was made and floral visitors was determined by direct observation Identifying insects at the level of families was conducted in the laboratory of entomology Tropical Experimental Station Pichilingue INIAP with the help of entomological keys, using a magnifying glass, and a stereo. the Simpson diversity index Jaccard similarity index was calculated. The highest percentage of insects found grouped in the Hymenoptera order with 76.99%. While Diptera visiting the flowers cocoa belong to the family of Cecidomyiidae, during the morning between 9h:00 and 11h:00 am. Simpson index of dominance and diversity is 0.58 and 0.42 respectively. According to the similarity index of Jaccard there was a 24% similarity between the families of insects found in the two production systems.